Addressing Fraction Learning Challenges: Developing Contextual Student Worksheets to Strengthen Numeracy Literacy in Junior High School - Komarudin, Komarudin; Wandira, Dea Ayu; Putri, Agustiany Dumeva; Hutkemri, Hutkemri; Suherman, Suherman; Mohd Shahali, Edy Hafizan Bin; Puspita, Laila (RANGE: Jurnal Pendidikan Matematika, 2025)
Numeracy literacy is a critical competency in mathematics education, but students often have difficulty understanding the concept of fractions contextually. This study aims to develop Student Worksheets based on Contextual Teaching and Learning (CTL) to improve numeracy literacy in fractions at the junior high school level, emphasizing the integration of real-life contexts and curriculum relevance. This study uses the Design Research method with the Tessmer formative evaluation approach, involving 28 seventh grade students of MTs YPNH Tanah Abang, Palembang. The stages include needs analysis, prototype design, expert validation (materials and media), and gradual trials (one-to-one, small group, and field test). Data were collected through questionnaires, interviews, and learning outcome tests, analyzed qualitatively-quantitatively to assess the validity, practicality, and effectiveness of the student worksheets. The results of the study stated that the student worksheets were declared valid based on expert assessments and very practical according to student responses. The effectiveness of the student worksheets was proven by the average class value which was included in the "Very Good" category and the high percentage of learning completion. Analysis of students' answers showed an increase in students' ability to apply fraction concepts in authentic contexts, such as visual data analysis and predictions based on quantitative information. This study contributes to the selection of CTL-based student worksheets in improving students' numeracy literacy through real problems and empirically valid structured frameworks, in accordance with the principles of the Independent Curriculum.